Thermal fatigue behavior of new ceramic thermal barrier coatings obtained by the atmospheric plasma spray process (2016)
The development of new ceramic materials to protect the metallic components against corrosion and oxidation at high temperature, also known as thermal barriers coating (TBC), is of a great interest topic for many industrial and consumer sectors, such as energy generation, aeronautics and automotive industries.This paper carried out a study on the thermal fatigue behavior of the bond coat, by centering the answer in one of the components which constitute a TBC: the anchor coat. The different TBC components were deposited by an Atmospheric Plasma Spraying (APS) Technique. Microstructure and anchor coat composition along the thermal cycles were studied.